Some aspects of professional youth self-determination - Завгородня, Н. М. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2017)
It was analyzed the surveys results of different aged students, who are studying in Kharkov universities. Addressed factors that have the greatest impact on the graduates’ career choices and change their attitude towards their chosen profession during the learning process. Identified the problems in the career-oriented work, allocated areas for further refinement.